Determination of Typical Values for Pediatric Head CT Scan at Universitas Andalas Hospital - Fardela, R.; Delvihardini, R.; Pratama, I. B. G.P.; Milvita, D.; Oktavia, A. (National Research and Innovation Agency, 2025)
The utilization of X-rays in the Computed Tomography Scaner (CT scan) modality has proliferated for diagnostic purposes. CT scans deliver higher doses than other modalities, consequently protecting patients from excessive radiation doses is necessary by increasing optimization efforts in patients, especially pediatric patients. This research aims to determine the typical value and analyze the correlation of age, body mass, and exposure factor (mAs) to Computed Tomography Dose Index Volume (CTDIVol) and Dose Length Product (DLP). The typical dose value was obtained from the median value (Q2) using data derived from pediatric patients undergoing a head CT scan with a total of 33 patients at Universitas Andalas Hospital, with a correlation determined using a linearity test. The results obtained were the typical value for CTDIVol of 31.1 mGy and DLP of 793.3 mGy.cm. There is a moderate correlation between age and CTDIVol and DLP values, a high correlation between body mass and CTDIVol and DLP values, and a very high correlation between the exposure factor (mAs) and CTDIVol and DLP values.